Optimization of activated carbon production from empty fruit bunch fibers in one-step steam pyrolysis for cadmium removal from aqueous solution - Al-Khatib, Ma'an Fahmi Rashid; Muyibi, Suleyman Aremu; Amode, Jeminat Omotayo (Springer, 2011)
The fast growth of the palm oil industry in Malaysia is associated with various waste products, namely the empty fruit bunches (EFB), which have a negative impact on the environment. Therefore, these wastes were utilized as a cheap raw material for the production of activated carbon (AC) with less energy consumption. One step steam pyrolysis was used to produce AC from oil palm empty fruit bunch fibers (EFBF) by varying the operating parameters of temperature, steam flow rate, and activation time using two-level full factorial experimental design (FFD). Ten samples of AC were prepared and the optimized production conditions were chosen based on the ability to adsorb and remove cadmium. Physical activation comprised of carbonization for 30 min using nitrogen gas (N2), followed by activation with steam at different flow rates (2.0, 3.0, and 4.0 ml/min), temperatures (600, 750,and 900C) and times (15, 30, and 45 min). The AC sample produced at an activation temperature of 900C with a steam flow rate of 2.0 ml/min and activation time of 15 min was selected as the best adsorbent with a total yield of 21.7%. It had adsorbed more than 97% of total cadmium from aqueous solution within 2 min of the contact time. Characterization of EFBF-based AC by SEM and BET surface area analysis had shown a good-quality adsorbent with highly active sites and well-developed pores with BET surface area of 635.16 m2/g. Experimental results indicated that the prepared AC from EFBF provide a promising solution in water and wastewater treatment